Principles of cytokine-receptor interactions and signal transduction - Li, Xiaoxia (Henry Stewart Talks, 2012)
Cytokine receptor signal transduction, Role of cytokines in the immune system -Classification of cytokines and cytokine receptors, Receptors with intrinsic kinase activity (TGF-TGFR family), Cytokine receptors directly recruit kinases (The four-alpha-helix bundle cytokine family; JAK-STAT signaling), Cytokine receptors recruit kinases through adaptors (IL-1R and IL-17R), Specificity of cytokine signaling, Update talk: Myddosomes in TLR-IL-1R signaling, Update talk: IRAK2 kinase domain, Update talk: IL-17 signaling pathways, Update talk: Act1 as an RNA binding protein, Update talk: IL-17A induces Act1 binding to pro-inflammatory mRNAs
Updated at 2024/03/31